PENGARUH METODE PERLAKUAN DALAM PERAWATAN BETON TERHADAP KUAT TEKAN DAN DURABILITAS BETON - Supriani, Fepy; Islam, Mukhlis (Inersia: Jurnal Teknik Sipil, 2017)
Concrete strength is influenced by several variables, among others by its constituent material, mix design, workmanship, and curing. The objective of concrete curing is to maintain the concrete in certain conditions after the dismantling of the formwork hence the optimization of concrete strength can be achieved close to the designed strength. This study aims to determine the effect of concrete curing on its compressive strength. Designed concrete compressivestrength of 20 MPa with slump values of 60-100 mm to be used. The specimens are cube-shaped with 15 cm dimension. Concrete compressive strength tests were conducted at 28 days and 56 days of concrete age. The types of concrete curing consist of 9 variations, i.e., not treated, water immersed and water sprinkling. Optimum 28 days age of compressive strength of concrete obtained from specimens that immersed in fresh water, which was 31,3 MPa. The concretespecimens that were put outdoor without any curing and treatment generates second highest compressive strength value of 28.6 MPa. The 28 days age of concrete compressive strength values cured with water sprinkling with addition of burlap wrapping are still under the compressive strength of uncured concrete. Significant changes to the strength of cured concrete occurred at age of 56 days and uncured concrete strength decreased up to 19%. The optimum increase occurred in concrete cured with burlap sack wrapping and water sprinkling that was conducted routinely for 3 days by 27,84%. With increasing age (durability) the treated concrete has better strength.